Factors Associated with Stunting Prevention Among Children Aged 24–59 Months in The Working Area of Ternate City Health Centers - Galapu Sangadji; Andiani Andiani; Rosmila Tuharea; Agustin Rahayu; Nani Supriyatni (UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2026)
Stunting is a chronic nutritional problem caused by prolonged nutritional deficiencies during the first 1,000 days of life and can impair physical growth, cognitive development, and future productivity. This study aimed to examine the relationship between maternal knowledge, diarrhea incidence, acute respiratory infection (ARI), exclusive breastfeeding, and environmental sanitation with stunting prevention efforts among children aged 24–59 months in the working area of Ternate City Health Centers in 2025. An analytic observational study with a cross-sectional design was conducted. A total of 87 respondents were selected from 680 children using the Slovin formula and purposive sampling. Data were collected through structured interviews, environmental sanitation observation, and height measurement using a microtoise according to WHO standards. The data were analyzed using the Chi-square test with α = 0.05. The results showed that diarrhea incidence (p = 0.010) and exclusive breastfeeding (p = 0.000) were significantly associated with stunting prevention efforts, while maternal knowledge (p = 0.619), ARI incidence (p = 0.231), and environmental sanitation (p = 0.994) were not. These findings suggest that stunting prevention should prioritize exclusive breastfeeding promotion and diarrhea prevention through breastfeeding counseling, nutrition education, growth monitoring, and clean and healthy living behavior promotion at community health centers and integrated health posts. Limitations include the cross-sectional design, which precludes causal inference, purposive sampling, which may cause selection bias, and self-reported data, which may be affected by recall bias.